Genetic association and characterization of FSTL5 in isolated clubfoot. (26th October 2020) - Khanshour, Anas M; Kidane, Yared H; Kozlitina, Julia; Cornelia, Reuel; Rafipay, Alexandra; De Mello, Vanessa; Weston, Mitchell; Paria, Nandina; Khalid, Aysha; Hecht, Jacqueline T; Dobbs, Matthew B; Richards, B Stephens; et al.
Abstract: Talipes equinovarus (clubfoot, TEV) is a congenital rotational foot deformity occurring in 1 per 1000 births with increased prevalence in males compared with females. The genetic etiology of isolated clubfoot (iTEV) remains unclear. Using a genome-wide association study, we identified a locus within FSTL5, encoding follistatin-like 5, significantly associated with iTEV. FSTL5 is an uncharacterized gene whose potential role in embryonic and postnatal development was previously unstudied. Utilizing multiple model systems, we found that Fstl5 was expressed during later stages of embryonic hindlimb development, and, in mice, expression was restricted to the condensing cartilage anlage destined to form the limb skeleton. In the postnatal growth plate, Fstl5 was specifically expressed in prehypertrophic chondrocytes. As Fstl5 knockout rats displayed no gross malformations, we engineered a conditional transgenic mouse line ( Fstl5 LSL ) to overexpress Fstl5 in skeletal osteochondroprogenitors. We observed that hindlimbs were slightly shorter and that bone mineral density was reduced in adult male, but not female, Prrx1 -cre; Fstl5 LSL mice compared with control. No overt clubfoot-like deformity was observed in Prrx1 -cre; Fstl5 LSL mice, suggesting FSTL5 may function in other cell types to contribute to iTEV pathogenesis. Interrogating published mouse embryonic single-cell expression data showed that Fstl5 was expressed in cell lineage subclusters whose transcriptomes were associated with neural system development. Moreover, our results suggest that lineage-specific expression of the Fstl genes correlates with their divergent roles as modulators of transforming growth factor beta and bone morphogenetic protein signaling. Results from this study associate FSTL5 with iTEV and suggest a potential sexually dimorphic role for Fstl5 in vivo .